Medium and mediality in Anne Carson. Issue 7 (3rd July 2022) - Bell, Al
ABSTRACT : Anne Carson's recent work has experimented with intermedia composition, leaving behind what one reviewer calls `the medium of the ordinary book'. While her critical reception often considers these experiments in relation to new media, I argue that we understand Carson in the context of a reflection on the concept of medium as such. This kind of reflection on medium is evident both in contemporary poetic experiment and recent work in poetics which consider medium as the locus of historical practice. By articulating the constraints of her linguistic medium Carson introduces difference in her work. Medium emerges as a hybrid concept, encompassing apparatuses of mediation; conventions; and the mediality or impart-ability (Benjamin) of language as a social practice. The article charts these aspects of medium in Nox and Autobiography of Red, focusing on medium as a physical substrate, ekphrasis and translation, recurring elements in Carson's work concerned with mediality: the means of representation, address, figuration and communication. I conclude by suggesting that through these engagements with medium the historical nature of the work emerges, and, consequently, its means of differing from the present; this represents a resource against what Rosalind Krauss calls `the deadening embrace of the general' in contemporary art.